Strategi Dan Model Pendekatan Pendidikan Karakter - Yossita Wisman; Cukei Cukei (FKIP Universitas Palangka Raya, 2020)
Education is a way for humans throughout their lives to become a means of transmitting and transforming values and knowledge. In the frame of instilling the character of the nation, excluded from education. Character education is important for human life, so the role played by the education world does not only show moral knowledge, it is also agreed to accept and be willing to take real moral actions. The problem of character or morality has become a common problem. Character crisis that is marked by reality in society, it really happened. Not only that, a crisis of trust also occurs in the elite community groups, namely corruption that is increasingly rampant. This demoralization is because the learning process that facilitates moral education and character is merely textual and does not prepare learners to respond to contradictory lives.